2020
DOI: 10.24843/soca.2020.v14.i01.p02
|View full text |Cite
|
Sign up to set email alerts
|

Peran Asosiasi Aspakusa Makmur Boyolali Dalam Pemberdayaan Petani

Abstract: The vegetable farmers need an effort to increase their ability so they can produce the optimal quantiity and quality vegetables for meet an increasing demand. Aspakusa Makmur Boyolali  is an agribusssines association that seeks to self farmer so that market demand can be met.This reasearch aims was to analyze the role of the Aspakusa Makmur Boyolali Association in to improve self relience anoy farmers. The role of the Association of Aspakusa Makmur Boyolali in empowerment can be seen through empowerment strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Farmers have the authority to choose their agricultural operations, planting times Following this matter, a partnership companion is a third party who acts as a mediator, facilitator, and institutional empowerment for partners. Muna et al 2020) stated that the farmer empowerment strategy simultaneously plays a role in the independence of members and that counseling and mentoring strategies, as well as strategies for easy access to science and technology, are partially the variables that affect the independence of members. As a result, collaborating partners are universitybased young researchers taught and accompanied by specialists from diverse scientific disciplines (Table 2).…”
Section: Authority Bordermentioning
confidence: 99%
“…Farmers have the authority to choose their agricultural operations, planting times Following this matter, a partnership companion is a third party who acts as a mediator, facilitator, and institutional empowerment for partners. Muna et al 2020) stated that the farmer empowerment strategy simultaneously plays a role in the independence of members and that counseling and mentoring strategies, as well as strategies for easy access to science and technology, are partially the variables that affect the independence of members. As a result, collaborating partners are universitybased young researchers taught and accompanied by specialists from diverse scientific disciplines (Table 2).…”
Section: Authority Bordermentioning
confidence: 99%
“…LMDH was established to carry out forest management in the Community Collaborative Forest Resource Management (PHBM) system which includes the following aspects: a) strengthening and developing institutions, b) participatory planning of swaths of forest village region (HPD), c) criteria and indicators for the sustainability of forest resources, and d) monitoring and evaluation (Wartiningsih and Nunuk Nuswardani, 2015) The role of the Aspakusa Makmur Boyolali Association in empowering its members and achieving member independence plays a great role and is categorized as high. The role of the Aspakusa Makmur Boyolali Association in empowering its members through farmers' empowerment strategies simultaneously plays a role in achieving member independence (Muna et al, 2020).…”
Section: Role Of Lmdh (X4)mentioning
confidence: 99%
“…The National Socio-Economic Survey of Statistics Indonesia of Bali Province from 2016 to 2017 showed that the order of the foodstuff groups (staple food) with the highest consumption level after grains was vegetables. Muna, et al (2020) stated that the high and increasing demand for vegetables in Indonesia encourages farmers to produce vegetable crops of optimal quality and quantity. Bali Province, which is frequently considered a tourist destination, can establish vegetable selling businesses to meet tourism needs.…”
Section: Introductionmentioning
confidence: 99%